Prevalence and determinants of e-cigarette use among vocational college students: a cross-sectional study - Mohd Shoaib, Siti Munisah; Ahmad, Norliza; Mahmud, Aidalina (Public Library of Science, 2025)
Introduction E-cigarette use is rising globally, particularly among young adults, posing increasing health risks. This study examined the prevalence and factors associated with e-cigarette use among diploma students in a Malaysian vocational college. Methodology A cross-sectional study was conducted among 700 students using probability proportionate to size sampling and a validated online questionnaire. Logistic regression identified factors associated with e-cigarette use, with p < 0.05 considered statistically significant. Results The response rate was 87.7%, with an e-cigarette use prevalence of 29.0%. Significant factors included male gender (aOR = 5.2, 95% CI: 2.7–10.1), Sabah and Sarawak Bumiputera ethnicity(aOR = 83.1, 95% CI: 2.2–3146.3), perceived e-cigarette aids in quit smoking (aOR = 1.6, 95% CI: 1.2–2.1), perceived e-cigarette does not contain the toxic chemicals found in conventional cigarette (aOR = 1.4, 95% CI: 1.0–2.0), having close friends who use conventional cigarette (aOR = 2.1, 95% CI: 1.0–4.1) or e-cigarette (aOR = 8.0, 95% CI: 2.3–28.1), television exposure (aOR = 2.1, 95% CI: 1.0–4.2), positive attitude towards e-cigarette (aOR = 1.2, 95% CI: 1.1–1.2), and higher willingness (aOR = 1.2, 95% CI: 1.0–1.3) and intention (aOR = 1.4, 95% CI: 1.2–1.5) to use. Conclusion E-cigarette use among students was influenced by gender, ethnicity, risk perceptions, peer influence, and media exposure. Targeted interventions addressing these factors are essential for reducing e-cigarette use in this population.